(untitled) - S Kantharaj Naik; S.A. Premchand; W Benjamin (Academia Anatomica International, 2020)
Background: Knowledge of the branching pattern of arch of aorta is important in avoiding surgical and accidental injuries during aortic instru- mentation, thoracic and neck surgeries. Subjects and Methods: The present study is based on dissections that were performed on 50 properly embalmed human cadaver specimens. The anatomical variations of arch of aorta and its branches, diameter of its branches at site of origin and distance of each branch from the point of origin to median plane were measured. Results: The usual three branched pattern of arch of aorta was found in 36 specimens (72%). The common trunk for both brachiocephalic trunk and left common carotid artery was present in 10 specimens (20%). In 2 specimens (4%), the arch gives four branches, left vertebral artery being additional branch. In 1 specimen (2%), the arch gives three branches namely; common trunk for brachiocephalic trunk and left common carotid artery, left vertebral artery and left subclavian artery. In 1 specimen (2%), the arch gives three branches namely; brachiocephalic trunk, left common carotid artery and common trunk for left vertebral artery and left subclavian artery. Conclusion: The results in this study provide significant information vital for anatomists, cardiovascular surgeons and radiologists.